Measuring Cost Efficiency of Ukrainian Banks in 2008 - Pilyavskyy, Anatoliy; Matsiv, Yuriy; Vovchak, Olga (Comparative Economic Research. Central and Eastern Europe, 2013)
The paper presents the results of a stochastic frontier analysis (SFA) of cost-efficiency of Ukrainian banks. As of lack of data on the personnel costs, we had to set limits to the year of 2008 only. To modeling banking activity, we apply the intermediary approach as one of the most commonly used in literature. Considering the results of statistical tests, we chose translog functional form of cost function and half–normal distribution of random inefficiency term. As a result of the research, we found out that efficiency of Ukrainian banks varies within 0.5224 and 0.9869 with an average value of 0.8734. Having checked a range of hypotheses, we discovered insignificant distinctions among banks by their size, type of owner and location.